Some of the possible influences and causes of deindustrialization in Brazil (International Seven Journal of Multidisciplinary, 2024)
The causes and influences of deindustrialization in Brazil are directly related to the context of the beginning of global industrialization. Thus, in this study we undertook a bibliographical and electronic review of a discussion on the factors of industrialization and the correlation of political, economic and social factors with the deindustrialization of Brazil in contemporary society. Thus, the problematization established in this work corresponds to the following question: What are some of the possible influences and causes of deindustrialization in Brazil? Faced with this question, we set ourselves the general objective of demonstrating some of the possible influences and causes of deindustrialization in Brazil. Furthermore, deindustrialization needs to be combated in its negative aspect, as it demonstrates a disparity in investments and low competitiveness in domestic sectors such as services and agribusiness. As a country of excellence in the agribusiness sector, systematic investment is essential to balance the national “surplus” with industrial interests. Managing the abundant natural supply of raw materials is of the utmost importance for achieving expansionary levels in the economy. In turn, industrialization can propel Brazil even further towards first-world development.